Paciente femenino de 69 años de edad con neumonía desconocida. - Romero Espinoza, Freddy Nicolás (2021)
Community-acquired pneumonia (CAP) is defined as an acute infection of the lung parenchyma in a patient who has acquired the infection in the community, as opposed to hospital-acquired (nosocomial) pneumonia (PAH). COVID-19 is currently a common cause of pneumonia, for which the exact treatment is unknown, however, good patient management could reduce the risk of suffering its complications. Next, we present a case of a 69-year-old female patient who came to the clinic for presenting dyspnea grade 3 according to the mMRC scale. Being one of the first cases in Ecuador, the management of the disease is described here, having evolved favorably.